Programa quinquenal de eliminación de la rabia humana en una provincia con rabia canina endémica en Tailandia - T. Kamoltham; J. Singhsa; U. Promsaranee; P. Sonthon; P. Mathean; W. Thinyounyong (Bulletin of the World Health Organization)
A five-year project to prevent human deaths from rabies in Phetchabun Province, Thailand involved increasing accessibility of post-exposure treatment with the Thai Red Cross intradermal (2-2-2-0-1-1) regimen for humans exposed to potentially and confirmed rabid animals; intensifying documentation of post-exposure treatment; increasing educational awareness through advocacy in provincial schools, television programmes, and newspapers; reducing canine rabies by monitoring the dog population and implementing vaccination and sterilization programmes; increasing the cooperation between the Ministries of Public Health, Agriculture, and Education on a provincial level; and assessing the impact of the programme through intensified follow-up of patients exposed to suspected and laboratory-confirmed rabid animals. Between 1996 and 2001, 10 350 patients received post-exposure treatment; 7227 of these received the Thai Red Cross intradermal regimen. Fewer than 3% of exposed patients received rabies immunoglobulin. Seventy-three percent of all patients presented with WHO category III exposures. In a retrospective study, 188 patients exposed to laboratory-confirmed rabid animals were followed to determine their health status. Of these patients, 20 received the intramuscular Essen regimen and 168 the Thai Red Cross intradermal regimen (148 received 0.1 ml purified chick embryo cell rabies vaccine, 10 received 0.1 ml purified vero cell rabies vaccine, and 10 received 0.2 ml purified duck embryo cell rabies vaccine). All patients were alive one year after exposure. Two human deaths occurred in the first two years of the programme - neither patient had received vaccine or rabies immunoglobulin after exposure. No deaths occurred during the last three years of the programme, which indicated that the programme was successful.